Efektivitas Pengelolaan Kelas dengan Menerapkan Pembelajaran Berdiferensiasi untuk Meningkatkan Kualitas Pembelajaran Matematika di SD Negeri Laweyan Surakarta - Rifqi Tiara Febriyanti; Dita Siti Barokah; Sri Sri Marmoah; Yulia Suryani (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
There are indications of low learning outcomes so that innovation is needed in mathematics learning to improve the quality of learning. The purpose of this study was to improve the quality of learning in cognitive learning outcomes and learning activities of students in mathematics subjects of grade 5 of Laweyan Elementary School No. 54 Surakarta using differentiated learning. The method used in this study used classroom action research (CAR) with the Kemmis and Mc Taggart model. This study was conducted in two cycles and each consisted of four stages, namely planning, implementation (action), observation, and reflection. The data collected included cognitive learning outcomes obtained through tests and observation data regarding teacher and student activities during the learning process. The results showed that in cycle I, the classical completion rate achieved was 64.28% with a less category. However, in cycle II the success indicator was achieved with a classical completion rate reaching 85.71% with a good category. Then, in the observation of student activities in cycle I reached a percentage of 66% and in cycle II reached a percentage of 91%. Therefore, learning in cycle II has met the indicators of success with minimal classical learning completion. This finding shows that the application of learning that the application of differentiated learning significantly improves learning outcomes and student and teacher activities.